Answer:
loser
Step-by-step explanation:
hahahahaha
First we need to find inverse function of f(x) which is written in a form of (f(x))^(-1)
That means that we are actually looking for function f(y) and we need to solve this equation for "y"
y=(4x + 1)/3
3y = 4x + 1
4x = 3y - 1
x = (3y - 1) / 4
f(y) = (3y - 1)/4
Now we simply put the value of 3 instead of y and find the answer:
f(y=3) = (3*3-1)/4 = 2
Answer is 2
Answer:
Aidan eats 2 ice cream and makes 100$
Step-by-step explanation:
Answer:
-3+13x=9.
13x=9+3
13x=12
x=12/13
i proved it by putting value of x in reactant side you get product .
-3+13×12/13=9
After using the slope formula your answer would be 5/0.1 but when simplifying your answer is 50